(untitled) (Global Journal of Management and Business Research, 2023)
Abstract- Saudi Arabia has come a long way in developing its economy with Vision 2030 as its goal to achieve economic transformation Prior to implementing Vision 2030 Saudi Arabia had faced many issues which led to the imbalance of its economy Instigating Vision 2030 led to a drastic change in the tourism sector Attracting international investments led to focusing on various sectors like renewable energy entertainment and so on Even though the tourism sector lacked diversity initially after the implementation of Vision 2030 non-related economic segments flourished